Анализ распространенности эндометрита и эффективности методов его лечения - Aksionov V. V. (Научное и образовательное пространство: перспективы развития, 2016)
This article is devoted to the study of inflammatory diseases of the female reproductive system, especially endometritis and chronic endometritis. Endometritis in modern conditions is a common pathology among inflammatory diseases of female genital organs and leads to the development of various complications, sometimes fatal, and reproductive dysfunction that is certainly important medico-social significance. The author studied the methods of diagnosis and treatment of this disease. To reduce th
Keywords: заболеваемость; morbidity; эндометрит; воспалительные заболевания; органы малого таза; endometritis; inflammatory diseases of the pelvic organs